2022
DOI: 10.3390/microorganisms10081502
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Two Jaculus Rodents as Potential Reservoir Hosts of Leishmania Parasites in Tunisia

Abstract: This study shows, for the first time, natural Leishmania infection among Jaculus spp. in an endemic region of Tataouine, South Tunisia. To better characterize the transmission cycles in this complex focus of mixed transmission, Leishmania detection and species identification were performed by direct examination, internal transcribed spacer-1 (ITS1)-PCR-restriction fragment length polymorphism (RFLP), and sequencing of Jaculus (J.) jaculus (Linnaeus, 1758) and J. hirtipes (Lichtenstein, 1823) rodent species, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Two manuscripts have provided new insights into Leishmania ecology of with updated evidence of infection in rodents [ 7 ] and Iberian lynxes [ 8 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two manuscripts have provided new insights into Leishmania ecology of with updated evidence of infection in rodents [ 7 ] and Iberian lynxes [ 8 ].…”
mentioning
confidence: 99%
“…Ghawar et al reported natural Leishmania infections in 46 rodents of the genus Jaculus from Tataouine governorate, where leishmaniasis is endemic, in southern Tunisia [ 7 ]. Parasites were observed in 19 (41.3%) smears, while parasitic DNA was detected in 28 (60.9%) spleen samples.…”
mentioning
confidence: 99%